2014
DOI: 10.1186/2041-9139-5-12
|View full text |Cite
|
Sign up to set email alerts
|

Development and staging of the water flea Daphnia magna (Straus, 1820; Cladocera, Daphniidae) based on morphological landmarks

Abstract: BackgroundCrustaceans of the genus Daphnia are one of the oldest model organisms in ecotoxicology, ecology and evolutionary biology. The publication of the Daphnia pulex genome has facilitated the development of genetic tools to answer long-standing questions in these research fields (Science 331: 555-561, 2011). A particular focus is laid on understanding the genetic basis of the striking ability of daphnids to change their phenotype in response to environmental stressors. Furthermore, Daphnia have recently b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 21 publications
1
47
0
Order By: Relevance
“…A more thorough understanding of the exact localization of PSNPs in or on lipid droplets, respectively, might be of interest for future studies. Here, we observed that the eggs start to internalize PSNP after being in the brood pouch from stage 2 onwards, thus in early embryogenesis while the embryos are still in the chorion shell (Mittmann et al 2014;Giardini, Yan, and Heyland 2015). This suggests that, in contrast to the observed protective role of chorion in fish (Fent et al 2010), the chorion of crustacean embryos does not play a protective role for NP exposure.…”
Section: Discussionmentioning
confidence: 67%
“…A more thorough understanding of the exact localization of PSNPs in or on lipid droplets, respectively, might be of interest for future studies. Here, we observed that the eggs start to internalize PSNP after being in the brood pouch from stage 2 onwards, thus in early embryogenesis while the embryos are still in the chorion shell (Mittmann et al 2014;Giardini, Yan, and Heyland 2015). This suggests that, in contrast to the observed protective role of chorion in fish (Fent et al 2010), the chorion of crustacean embryos does not play a protective role for NP exposure.…”
Section: Discussionmentioning
confidence: 67%
“…In contrast, the oldest neonates had a 3.8‐fold shallower concentration–response curve (as indicated by the slope) and a 4‐fold greater variability around the average Cd EC50 (as indicated by the CV ) within a 4‐h age window. These results may suggest that the daphnids were released from the parent daphnid with a physiological defense mechanism ; however, such a mechanism might have waned as they aged and the neonates became susceptible to a variety of external factors that may have led to increased variability in the susceptibility to some metals. Alternatively, Cd (and to some extent Zn) might have interfered with important age‐dependent developmental/physiological processes that occur between 48 h and 72 h postbirth (i.e., after a test started with daphnids 0–4 h old had ended, when the daphnids were 48–52 h old, but before a test started with daphnids 20–24 h old had ended, when the daphnids were 68–72 h old).…”
Section: Resultsmentioning
confidence: 99%
“…The studies on the cell division patterns of some Dendrobranchiata, Caridea, Euphausiacea, and Branchiopoda have used whole mounts Scholtz 2004 , 2014 ;Hertzler 2005 ;Biffi s et al 2009 ;Klann and Scholtz 2014 ), while for The branchiopod crustaceans undergo a direct development which results in juveniles that are morphologically similar to their adults. The left column illustrates major events of embryonic development which takes place in the dorsal brood pouch of the mother (Based on Mittmann et al ( 2014 )). Scale bars: 100 μm.…”
Section: Invariant Early Cell Lineagesmentioning
confidence: 99%